2019
DOI: 10.1088/1674-1056/28/2/027401
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy (40 keV) proton irradiation of YBa 2 Cu 3 O 7− x thin films: Micro-Raman characterization and electrical transport properties

Abstract: To investigate the damage profiles of high-fluence low-energy proton irradiation on superconducting materials and related devices, Raman characterization and electrical transport measurement of 40-keV-proton irradiated YBa 2 Cu 3 O 7−x (YBCO) thin films are carried out. From micro-Raman spectroscopy and x-ray diffraction studies, the main component of proton-radiation-induced defects is found to be the partial transition of superconducting orthorhombic phase to the semiconducting tetragonal phase and non-super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…This is owing to the displacement energy of oxygen atoms in the Cu-O chains is much lower than that of oxygen atoms in the CuO 2 planes [31]. But it has been proved that a decrease in the transition temperature T c with the increase in the fluence of proton irradiation after the fluence of 1×10 14 p cm −2 , which indicates that oxygen defects in CuO 2 planes with cumulative irradiation [32]. Especially, there is no observed zero-resistance after a fluence of 1×10 15 p cm −2 [32].…”
Section: Superconducting Transition Temperature T C and Critical Curr...mentioning
confidence: 99%
“…This is owing to the displacement energy of oxygen atoms in the Cu-O chains is much lower than that of oxygen atoms in the CuO 2 planes [31]. But it has been proved that a decrease in the transition temperature T c with the increase in the fluence of proton irradiation after the fluence of 1×10 14 p cm −2 , which indicates that oxygen defects in CuO 2 planes with cumulative irradiation [32]. Especially, there is no observed zero-resistance after a fluence of 1×10 15 p cm −2 [32].…”
Section: Superconducting Transition Temperature T C and Critical Curr...mentioning
confidence: 99%
“…Raman spectroscopy is a powerful tool to probe the microstructure of thin films and its relationship with other physical properties of oxides. [15,16] In past decades, Raman spectroscopy has been widely employed to study the structure of Fe 3 O 4 films. [8,9,17] films.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on proton irradiation have already been demonstrated to create random point defects [125][177], which can create c-axis peak enhancements at low temperatures and high magnetic field regimes [116] (dE/dx) can be compared to previously experimentally established graphs [123] that display the ranges of energy loss values required to create defects of different morphologies. By utilising this information, we can identify the specific energy range required for heavy ion irradiation to create a defect with the desired morphology.…”
Section: Introductionmentioning
confidence: 99%
“…By utilising this information, we can identify the specific energy range required for heavy ion irradiation to create a defect with the desired morphology. However, in proton irradiation investigation, the information regarding the type of defects it can create is not required as previous research has shown that irradiation using protons creates point defects [125].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation